Topological Lifshitz Phase Transition in Effective Model of QCD with Chiral Symmetry Non-restoration - Huu Phat, Tran; Thu Ha, Phung Thi; Tuan Anh, Nguyen (Communications in Physics, 2013)
The topological Lifshitz phase transition is studied systematically within an effective model of QCD, in which the chiral symmetry, broken at zero temperature, is not restored at high temperature and/or baryon chemical potential. It is found that during phase transition the quark system undergoes a first-order transition from low density fully-gapped state to high density state with Fermi sphere which is protected by momentum-space topology. The Lifshitz phase diagram in the plane of temperature and baryon chemical potential is established. The critical behaviors of various equations of state are determined.